2021
DOI: 10.1029/2020jc016789
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Global Patterns of Seasonal Cycle in Sea Surface Salinity

Abstract: The advent of L-band passive microwave remote sensing in the last decade (2010 to present) has allowed for the first time the retrieval of global high-resolution sea surface salinity (SSS) from space (Reul et al., 2014;Vinogradova et al., 2019). These new SSS datasets have opened the modern era of salinity science, leading to new insights into the role of salinity in ocean circulation, water mass formation, the water cycle, and climate variability and change (Reul et al., 2020). Like many typical time series, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 101 publications
(138 reference statements)
2
9
0
Order By: Relevance
“…This result is in agreement with Yu et al. (2021)'s study using satellite‐ and in situ‐derived products. The broad maxima in σf2 ${\sigma }_{f}^{2}$ between (A) and (B), and between (G) and (H) can be understood as a consequence of seasonal changes in the rivers discharge.…”
Section: Space‐time Diagrams and The Seasonal Cyclesupporting
confidence: 93%
“…This result is in agreement with Yu et al. (2021)'s study using satellite‐ and in situ‐derived products. The broad maxima in σf2 ${\sigma }_{f}^{2}$ between (A) and (B), and between (G) and (H) can be understood as a consequence of seasonal changes in the rivers discharge.…”
Section: Space‐time Diagrams and The Seasonal Cyclesupporting
confidence: 93%
“…This is a result of the unique nature of the SSS field. It has a short spatial decorrelation scale due to the influence of rainfall and submesoscale variability [23], but is dominated in time scale by the seasonal cycle in many areas [35,38,39]. This can give those doing validation studies ways to formulate their space/time search criteria for optimum results (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. (2021) and Bingham et al. (2021) found that SSS annual and semiannual amplitudes are quite well represented over the open ocean by the satellite SSS products considered for building the CCI L4 SSS.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…The improved accuracy of the CCI L4 SSS with respect to individual sensor SSS accuracy has been made possible because individual sensor SSS products were already shown to detect consistent variabilities. For instance, D'Addezio and Subrahmanyam (2016) showed that SMOS and Aquarius detect high SSS variability associated with the Agulhas current consistent with Argo SSS, whereas Fournier and Lee (2021) showed very consistent SMOS and SMAP SSS in river plumes areas Yu et al (2021). andBingham et al (2021) found that SSS annual and semiannual amplitudes are quite well represented over the open ocean by the satellite SSS products considered for building the CCI L4 SSS.…”
mentioning
confidence: 99%